Raised from Obscurity: A Narratival and Theological Study of the Characterization of Women in Luke-Acts - Forbes, Greg (2016)
Anticipating Broader Narratival and Theological Themes in Luke-ActsChapter 4. Galilean Ministry (Luke 3:1-9:50); Jesus as the Central Narrative Character; Calling of the Disciples (Luke 5:1-11, 27-32; 6:12-16); Raising of the Widow's Son (Luke 7:11-17); Jesus anointed by a Sinful Woman (Luke 7:36-50); Women who Support Jesus (Luke 8:1-3); Jesus' True Family (Luke 8:19-21); Raising of Jairus' Daughter and the Healing of the Women with a Hemorrhage (Luke 8:40-56); Summary of Narratival Propositions; Theological Propositions; Anticipating Further Narratival and Theological Themes in Luke-Acts.